Cyanophage-encoded auxiliary metabolic genes in modulating cyanobacterial metabolism and algal bloom dynamics - Ain, Qurat ul; Wu, Kevin; Wu, Xuan; Bai, Qing; Li, Qiong; Zhou, Cong-Zhao; Wu, Qingfa (Frontiers in Virology, 2024)
Cyanophages play a pivotal role in controlling cyanobacterial populations in aquatic environments. These dsDNA viruses harbor auxiliary metabolic genes (AMGs) that modulate the key metabolic processes of their cyanobacterial hosts, such as Photosynthesis, nutrient uptake for the optimization of viral replication. Recently, pan1~pan5 and pam1~pam5 cyanophages have been isolated from the fifth largest water resource in China; Lake Chaohu. Detailed genomic analysis of these phages revealed that these isolated cyanophages especially Pan1, Pam2 and Pam3 possess unique AMGs that significantly enhance the metabolic activities of their hosts, potentially leading to the suppression of bloom formation and stabilization of the ecological dynamics of Lake Chaohu. Our findings provide concrete evidence that cyanophages encoding AMGs could serve as effective biocontrol agents against harmful algal blooms, offering a targeted approach to manage these environmental threats. The integration of cyanophage-based management therapies with traditional methods could advance the efficiency and sustainability of controlling cyanobacterial outbreaks, paving the way for novel applications in water resource management. This review emphasizes the importance and critical need for further exploration of phage-host dynamics to fully harness the potential of cyanophages in ecosystem regulation.